The political-administrative strategy of the emperor Theodosius II in Nestorius' appointment to the Episcopacy of Constantinople (428 AD) - de Figueiredo, Daniel [UNESP] (Universidade Federal do Rio Grande do Sul, 2020)
The aim of this article is to analyze the politico-administrative strategy of Emperor Theodosius II (408-450 AD) in the appointment of Bishop Nestorius to the Episcopacy of Constantinople in AD 428. This event led to the Nestorian Controversy, a theological conflict, which emerged within the ecclesiastical hierarchy of the Eastern Roman Empire, and sought to establish an orthodoxy regarding the manner in which the interaction between the human and divine natures occurred in the incarnate Christ. We perceived that the factions formed in the defense of the union of the two natures, advocated by bishop Cyril of Alexandria, and the separation of them, defended by Nestorius of Constantinople, had considered the presence of officials from the imperial administration in the dispute. Therefore our objective was to show that the reason Nestorius had been appointed to the Episcopacy of Constantinople by Theodosius II was related not only to the establishment of a project for religious unity, but also toward the complex politico-administrative game which included the consideration of interests and counterbalancing of powers among the aristocracies of officials who contributed to legitimize imperial unity.
A estratégia político-administrativa do imperador Teodósio II na convocação de Nestório para o episcopado de Constantinopla (428 d.C.)
Keywords: Eastern Roman Empire; Late antiquity; Nestorian controversy; Nestorius of Constantinople; Theodosius II